Respon ayam buras yang diberi campuran dedak halus, jagung kuning dan fermentasi ampas tahu terhadap bobot badan akhir ayam buras umur 0-8 minggu - Kastalani Kastalani; Herlinae Herlinae; Julio Terang (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2018)
The study aim to determine the effect of mixture level of rice bran, yellow corn and fermented tofu waste on final body weight of domestic poultry age 0-8 weeks. This study using randomized complete design with 4 treatments and 5 replications. The Treatment A = 80 % rice bran + 20 % yellow corn, B = 70 % rice bran + 20 % yellow corn + 10 % fermented tofu waste, C = 60 % rice bran + 20 % yellow corn + 20 % fermented tofu waste and D = 50 % rice bran + 20 % yellow corn + 30 % fermented tofu waste. The result showed that the provision of various level of a mixture not significant effect on final body weight of domestic poultry age 0-8 weeks.